HUBUNGAN PENGETAHUAN DENGAN SIKAP IBU HAMIL TENTANG AKTIVITAS SEKSUAL SELAMA KEHAMILAN DI KELURAHAN GAMBIR BARU KEC. KISARAN TIMUR TAHUN 2021 - Eliza Bestari Sinaga; Fifi Ria Ningsih Safari (MIDWIFERY HEALTH JOURNAL, 2021)
The need for sex for husband and wife in domestic life is an important element that can increase closeness and quality of life. Sexual intercourse during pregnancy is individual, depending on physical factors, emotions, sexual dysfunction and myths about sex during pregnancy. The purpose of this study was to identify the relationship between knowledge of pregnant women and attitudes of pregnant women about sexual activity during pregnancy. The design of this research is analytical with cross sectional design. With a sample of 50 pregnant women. The research was conducted in Gambir Baru Village, Kisaran Timur District, Asahan Regency. The research data was taken using a questionnaire, data processing by scoring, tabulating, editing, coding and then analyzed using the chi-square statistical test. The results showed that there was a relationship between knowledge of pregnant women and attitudes of pregnant women about sexual activity during their period. It is recommended for pregnant women to increase knowledge about sexual activity during pregnancy and add insight by finding out information about sexual activity during pregnancy through health workers, print media and electronic media.